Progression of histological lesions after ABO incompatible kidney transplantation - Guy, Pierre; Delas, Audrey; Esposito, Laure; Cointault, Olivier; Colombat, Magali; Congy-Jolivet, Nicolas; Raynaud, Marc; Kamar, Nassim; Del Bello, Arnaud (Frontiers in Immunology, 2022)
Recent large meta-analyses suggested a poorer long-term patients’ and grafts’ outcomes after ABO incompatible (ABOi) living-donor kidney transplantation (LDKT) compared to ABO compatible LDKT. However, little is known about the long-term histological pattern after ABOi LDKT. We compared the histological features observed on protocol biopsies from 03/11 to 11/19 in 94 ABOi LDKT (including 14 with preformed Donor Specific Antibodies, pDSAs), 27 LDKT ABO compatible (ABOc) with pDSAs, and 21 ABOc without pDSAs) during the first five years post transplantation. During the first 5 years post-transplantation, a progression of chronic lesions (patients with a ci >0 raised from 11% to 65%, p<0.0001, patients with a ct >0 raised from 29% to 78%, p<0.0001) was observed in ABOi LDKT without pDSAs. Histological patterns of evolution were comparable to those observed in ABOc kidney transplant patients. Microvascular inflammation was lower in ABOi LDKT without pDSAs compared to those with pDSAs (ABOi or ABOc). At last follow-up, 28 months, IQR (15-48) post-transplantation, 29 patients (36%) had a severe graft dysfunction (defined by a CKD-epi eGFR < 30 mL/min/1.73m²). The donor age was a predictive factor for the development of severe kidney allograft dysfunction at last follow-up (HR= 1.05, 95% CI [1.05-1.10], p= 0.03). Hence, long-term histological analysis of ABOi LDKT shows only an increase of chronic interstitial and tubular atrophy changes, without active lesions. These data confirm that ABOi LDKT programs can be securely developed.